Progress in Canadian Mechanical Engineering 2018
DOI: 10.25071/10315/35360
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbent-Adsorbate Pairs for Solar Thermal Energy Storage in Residential Heating Applications: A Comparative Study

Abstract: This paper investigates the feasibility of using different adsorbent-adsorbate pairs in a thermal energy storage cycle to store solar energy for residential heating applications in Canada. Silica gel, activated carbon, activated aluminum, zeolite-4A, zeolite-5A and zeolite-13X adsorbents paired with methanol and water adsorbates are considered. Calculations are made to determine the volume, mass and cost of the adsorbent-adsorbate pair required to heat a house with four occupants. Zeolite 4A-water and zeolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Notably, when the adsorbate is water, zeolite 13X has a higher net heat of adsorption than other adsorbents such as silica gel, activated alumina, zeolite 4A, and zeolite 5A, which reduces the volume of adsorbent required for TES applications. 17 Furthermore, there have been numerous studies reported in the literature which show zeolite 13X yields good results in adsorbent-based TES systems. 18,19 More details regarding the zeolite 13X used in this work are provided in Table S1 in the supplementary information.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, when the adsorbate is water, zeolite 13X has a higher net heat of adsorption than other adsorbents such as silica gel, activated alumina, zeolite 4A, and zeolite 5A, which reduces the volume of adsorbent required for TES applications. 17 Furthermore, there have been numerous studies reported in the literature which show zeolite 13X yields good results in adsorbent-based TES systems. 18,19 More details regarding the zeolite 13X used in this work are provided in Table S1 in the supplementary information.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Furthermore, during the recharging phase water can be delivered to the zeolite 13X beads by passing air through the adsorbent bed; the water vapor in the air is adsorbed as air flows through the adsorbent bed. Notably, when the adsorbate is water, zeolite 13X has a higher net heat of adsorption than other adsorbents such as silica gel, activated alumina, zeolite 4A, and zeolite 5A, which reduces the volume of adsorbent required for TES applications 17 . Furthermore, there have been numerous studies reported in the literature which show zeolite 13X yields good results in adsorbent‐based TES systems 18,19 .…”
Section: Methodsmentioning
confidence: 99%